Cultura, arte, acervos e coleções digitais: a produção, gestão e regime da informação por meio de sistemas autônomos, redes descentralizadas e tecnologia blockchain - Tadeus Mariano Mucelli Motta (2024)
This thesis questions the recurring absence of technological art collections that use the most diverse technologies in their production, in the historical scenario of contemporary society, from the perspective of memory institutions. It also provides evidence of the intrinsic characteristics of this type of collection, based on its information regime, production, and management model, which amplify a scenario of loss or constant modes of data, information, and knowledge transfer in the context of a post-digital society. A central actor paradigm is constructed. Various types of agents from one or more ecosystems centralize demands, and actions and place themselves in a precarious position in their public or private attributions, in the face of a complex scenario of material and immaterial production in an immanent digital culture and under an accelerationist digital economy and policy. The thesis is presented in a multidisciplinary way, given the context of related fields of knowledge, digital ontology, political economy of information, digital art and culture, digital humanities, economic accelerationist theory, as well as thematic subfields such as digitization, decentralization, blockchain, artificial intelligence, autonomous systems, peer-to-peer networks, among others. The research is exploratory and empirical observation, which applied the qualitative method, assigned in two main stages through the review of scientific literature, use of methods of content analysis of available databases, and discourse analysis through structured interviews with agents in different scenarios. Local knowledge (national scenario) that relates to the international context of some (theoretical-practical) examples, also justified by the absence or restriction of similar models for analysis in Brazil. The aim was to understand the ways, processes, regimes and uses of information in the implementation, organization and retrieval of art and digital heritage archives through autonomous agents, machine learning and the use of new technologies such as blockchain in decentralized networks (P2P) based on technical-theoretical, scientific and transdisciplinary models in the field of information science interfacing with the digital humanities. As a result, the thesis proposes the implementation of a decentralized theoretical-technical accelerationist model, made up of five stages of action and under guiding principles such as the digital information regime in the post-digital society, the use of new technologies and autonomous systems, the decentralization of collections, the constitution of a sharing economy in a P2P society model, and the introduction and incorporation into ongoing socio-technical accelerationist models, which allows the application of a physical, digital, semantic, pragmatic informational method.